(untitled) (LACCEI, 2024)
The present research was developed applying the Deming circle methodology and its 4 proposed phases, its general objective was to elaborate a poultry breeding process improvement plan to increase productivity in a company of the poultry sector, 2022. The research was of pre-experimental design and the following techniques were used: documentary analysis and observation. Among the main causes that affect productivity are: lack of updated procedures, inadequate ventilation, poor training, etc. As for the results obtained, we can mention: the increase in productivity by 7.6 (starting at 83.47). The Wilcoxon test showed that the differences in productivity were significant